Microfabrication of a high‐density, non‐neutral antimatter trap. (1st October 2014) - Narimannezhad, Alireza; Jennings, Joshah; Weber, Marc H.; Lynn, Kelvin G.
Abstract : A unique approach for the fabrication of long‐aspect ratio microtubes is presented for an antimatter trap. Conventionally, non‐neutral antimatter is stored using a Penning‐Malmberg trap, a single tube with aspect ratios being of the order of less than 10:1. Parallel microtubes with aspect ratios of 1000:1 have the potential to store many orders of magnitude more. The silicon industry has paved the way to microelectromechanical systems technologies which have been utilised in this research. Standard processes such as photolithography, deep reactive ion etching, sputtering and thermo‐compression bonding were all used; however, unique methods of these processes were developed to overcome many engineering challenges and realise successful trapping.